The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1038/onc.2012.14
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation silences miR-132 in prostate cancer

Abstract: Silencing of microRNAs (miRNAs) by promoter CpG island methylation may be an important mechanism in prostate carcinogenesis. To screen for epigenetically silenced miRNAs in prostate cancer (PCa), we treated prostate normal epithelial and carcinoma cells with 5-aza-2'-deoxycytidine (AZA) and subsequently examined expression changes of 650 miRNAs by megaplex stemloop reverse transcription-quantitative PCR. After applying a selection strategy, we analyzed the methylation status of CpG islands upstream to a subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(97 citation statements)
references
References 42 publications
2
93
0
2
Order By: Relevance
“…Talin2 is also downregulated by miR‐132, but miR‐132 expression is itself suppressed by promoter methylation in prostate cancer cells. This correlates with a worse prognosis, and the authors speculate that elevated talin2 levels may suppress cell death and increase metastasis 114. Talin2 upregulation has also been implicated in breast cancer tumorigenesis and metastasis 33, 53 driving more aggressive cell invasion.…”
Section: Talin2 In Disease and Developmentmentioning
confidence: 98%
“…Talin2 is also downregulated by miR‐132, but miR‐132 expression is itself suppressed by promoter methylation in prostate cancer cells. This correlates with a worse prognosis, and the authors speculate that elevated talin2 levels may suppress cell death and increase metastasis 114. Talin2 upregulation has also been implicated in breast cancer tumorigenesis and metastasis 33, 53 driving more aggressive cell invasion.…”
Section: Talin2 In Disease and Developmentmentioning
confidence: 98%
“…Reduced miR-132 expression in osteosarcoma was associated with advanced clinical stage, the presence of distant metastasis, resistance to chemotherapy, and poorer overall and disease-free survival (23). Formosa et al (21) demonstrated a correlation between low miR-132 levels in prostate cancer and lymph node invasion, a high Gleason score and a more advanced tumor stage. Restoration of expression of miR-132 in prostate cancer cells promoted cell death by anoikis, and impeded cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown to be upregulated and to function as an oncogene in squamous cell carcinoma of the tongue (15), colorectal cancer (16), pancreatic cancer (17), hemangioma (18) and chronic lymphocytic leukemia (19). By contrast, it was reported to be downregulated and to function as a tumor suppressor in hepatocellular carcinoma (20), prostate cancer (21), ductal carcinoma in situ of breast (22) and osteosarcoma (23). However, little is currently known regarding the association between miR-132 dysregulation and the clinicopathological characteristics of NSCLC, and the involvement of miR-132 in NSCLC progression remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The methylation of promoter sequences in the DNA causes epigenetic gene silencing through the obstruction of transcriptional activators in or near the promoter. Importantly, recent studies have shown that a number of microRNAs (miRNAs) are also epigenetically regulated in different types of cancers including PCa, [3][4][5] which is directly responsible for the regulation of coding mRNAs. The methylation of DNA in the promoter sequence of miRNAs causes decreased expression of miRNA, leading to increased expression of their target mRNAs and proteins.…”
Section: Introductionmentioning
confidence: 99%